1982
DOI: 10.1210/endo-110-5-1641
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Plasma Cortisol during the 24-Hour Sleep/Wake Cycle in the Rhesus Monkey*

Abstract: The 24-h pattern of plasma cortisol and changes induced by alterations of the sleep/wake cycle were studied in 12 male rhesus monkeys. The chair-living animals were chronically prepared with a right atrial catheter and electroencephalogram electrodes. Hormone (blood samples every 15 min) and continuous activity/electroencephalogram profiles were obtained from the adjacent room for 96 h (4 animals), 24 h or various shorter periods of time. Plasma cortisol showed a circadian rhythm with a late evening minimum (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…A separate analysis examining the effect of DHT doses compared individually to placebo on basal CORT in DOM female monkeys found that there was also a significant treatment by time effect on diurnal cortisol comparing the low-dose DHT with placebo (F (1, 3)=250.845, p=0.001) indicating a reversal in levels from 9 a.m. to 9 p.m. and a restoration of normal CORT circadian rhythm (see:(Plant, 1981; Quabbe et al, 1982) with low DHT treatment. High-dose DHT also restored circadian rhythm (F (1, 3)=95.531, p=0.002) and significantly lowered basal CORT (F (1, 3)=115.927, p=0.002).…”
Section: Resultsmentioning
confidence: 99%
“…A separate analysis examining the effect of DHT doses compared individually to placebo on basal CORT in DOM female monkeys found that there was also a significant treatment by time effect on diurnal cortisol comparing the low-dose DHT with placebo (F (1, 3)=250.845, p=0.001) indicating a reversal in levels from 9 a.m. to 9 p.m. and a restoration of normal CORT circadian rhythm (see:(Plant, 1981; Quabbe et al, 1982) with low DHT treatment. High-dose DHT also restored circadian rhythm (F (1, 3)=95.531, p=0.002) and significantly lowered basal CORT (F (1, 3)=115.927, p=0.002).…”
Section: Resultsmentioning
confidence: 99%
“…Cortisol and melatonin secretions span two opposing halves of the day in diurnal animals, so that the SCN may influence peripheral oscillators with two different hormones acting in a time-qualified manner. In diurnal mammals and humans, cortisol secretion begins in the middle of the night and reaches its zenith in the early morning near awakening, whereas melatonin secretion begins in the late evening and reaches its zenith early in the sleep-span (Mazzoccoli et al, 2011;Quabbe et al, 1982). On the contrary, in nocturnal animals, cortisol and melatonin are secreted during the same phase with respect to the light/dark cycle, as daily variations in plasma corticosteroid display maximal values at dusk (Atkinson & Waddell, 1997).…”
Section: The Circadian Timing Systemmentioning
confidence: 99%
“…Plasma levels of adrenocorticotrophin (ACTH), corticosteroids or both have been shown to vary episodically and with circadian periodicity in several species including man (Krieger, Allen, Rizzo & Krieger, 1971;Gallagher, Yoshida, Roffwarg et al 1973), rhesus monkeys (Quabbe, Gregor, Bumke-Vogt & Härdel, 1982), sheep (Fulkerson & Tang, 1979) and cattle (Thun, Eggenberger, Zerobin et al 1981). In each of these studies, hormonal profiles were characterized in blood samples collected at a frequency of every 5 to 30 min throughout the day.…”
Section: Introductionmentioning
confidence: 99%